Pengaruh Hiking Attributes Terhadap Sport Decision Di Taman Nasional Gunung Rinjani - Ridwanudin, Oce; Yuniawati, Yeni; Devananda, Y. K. (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2019)
Sport decision is a Sport Decision making process that becomes a basic consumption, mainly on Sport Tourism. TNGR os one Hiking Tour provider which is facing up the decrease in visit Decision of climb participant. On this research, thr independent variable (X) is Hikimg Attributes consisting of Physical Benefit, Mental Benefit, Facilitation of Trail and Information, the dependent variable (Y) is Sport Decision, The type of research used is descriptive varification, and the method used is explanatory survey with sample size 109 respondents. Techniques of data analysis an hypothesis testing used multiple linear regression, the result indicated the Hiking Attributes have a significant influence on Sport Decision. the most influential is Mental Benefit where TNGR has successfully made climb participant can reduce fatigue daily routines, so that make the participant feel the comfort and happy while Hiking on TNGR, the weakest factor is Facilitation Of Trail, this aspect needs tobe improved by cleanliness such as held the guidance about environment to climb participants, in addition officials can give a reward on the climbers that keep the environment